Fish, Marine n−3 Fatty Acids, and Atrial Fibrillation – Experimental Data and Clinical Effects - Rix, Thomas A.; Mortensen, Lotte M.; Schmidt, Erik B. (Frontiers in Physiology, 2012)
Marine n-3 polyunsaturated fatty acids (PUFA) may have beneficial effects in relation to atrial fibrillation (AF) with promising data from experimental animal studies, however, results from studies in humans have been inconsistent. This review evaluates the mechanisms of action of marine n-3 PUFA in relation to AF based on experimental data and provides a status on the evidence obtained from observational studies and interventional trials. In conclusion, there is growing evidence for an effect of marine n-3 PUFA in prevention and treatment of AF. However, further studies are needed to establish which patients are more likely to benefit from n-3 PUFA, the timing of treatment and dosages.